Environmental enforcement with endogenous ambient monitoring - Laurent Franckx (Fondazione Eni Enrico Mattei (FEEM), 2002)
We consider an inspection game between n polluting firms and an environmental enforcement agency. If the cost of monitoring ambient pollution is low enough, the optimal inspection policy consists in imposing the maximal possible fine, and mixing between observing ambient pollution and not conducting any inspection at all. However, with stringent upper limits on the fine, the agency mixes between observing ambient pollution and inspecting all firms. The observation of ambient pollution is always followed by sequentially rational firm inspections. Comparisons with Franckx (2002a,2002b) show that commitment power has a very strong impact on the value of prior information.
Keywords: K42; Q20; 330; environmental enforcement; ambient inspections; commitment; Umweltschutz; Umweltbelastung; Aufsichtsbehörde; Theorie; Rechtsdurchsetzung